2008
DOI: 10.2176/nmc.48.72
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Peripheral-Type Primitive Neuroectodermal Tumor -Case Report-

Abstract: A 15-year-old man presented with headache. Magnetic resonance (MR) imaging revealed a large extraaxial tumor with cyst at the right frontotemporal region. The solid part of the tumor was homogeneously enhanced on T 1 -weighted MR imaging after injection of gadolinium. Digital subtraction angiography of the external carotid artery revealed sunburst appearance corresponding to the tumor, which was fed by the right middle meningeal artery. His headache worsened and computed tomography revealed enlargement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 16 publications
(18 reference statements)
2
20
0
Order By: Relevance
“…(Table 2) [26]. Immunohistochemistry for CD99 is usually detected in ESFTs but is not detected in cPNETs [1,16,[21][22][23][24][25]. In our study we found CD99 positivity in 10 of 11ESFT cases (90%), and 2 of 7 cPNET cases were detected CD99 immunoreactivity, similar to the literature.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…(Table 2) [26]. Immunohistochemistry for CD99 is usually detected in ESFTs but is not detected in cPNETs [1,16,[21][22][23][24][25]. In our study we found CD99 positivity in 10 of 11ESFT cases (90%), and 2 of 7 cPNET cases were detected CD99 immunoreactivity, similar to the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Although extremely rare cases of olfactory neuroblastoma, small cell osteosarcoma, mesenchymal chondrosarcoma, polyphenotypic round cell tumor, desmoplastic small round cell tumor, neuroblastoma and rhabdomyosarcoma have been reported to contain either EWS/FLI1 or EWS/ERG fusion genes, the identification of these translocations is for the most part regarded as highly specific to ESFTs and is increasingly recognized as the "gold standard" for diagnosis [3,4,13,[17][18][19][20]. In contrast, such translocations are not found in cPNETs [1,2,16,[21][22][23][24][25]. Thorner et al reported that identification of the t(l1;22) (q24; q12) by cytogenetics should not be taken as absolute proof of a diagnosis of ESFTs in the absence of confirmatory histology to include positive staining for MIC2 [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the neurosurgical field, EWS/pPNETs occasionally occur in the meninges of the cranial vault, epidural space of the spinal canal, and cauda equina. 8,13) CD99 is a 30 or 32 kDa cell surface glycoprotein derived from the MIC2 gene. This molecule was initially isolated as an EWS antigen and so expression was considered pathognomonic for EWS/pPNET.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial occurrence of pPNET is extremely rare, and only a few cases have been reported to date. [3][4][5] We report a 16-year-old boy who presented with headache and gradual left-sided hearing loss.…”
mentioning
confidence: 99%